Green tea epigallocatechin-3-gallate inhibits platelet signalling pathways triggered by both proteolytic and non-proteolytic agonists - Deana, Renzo; Turetta, Loris; Donella-Deana, Arianna; Donà, Massimo; Brunati, Anna Maria; Michiel, Lucia De; Garbisa, Spiridione (Thrombosis and Haemostasis, 2003)
Epigallocatechin-3-gallate (EGCG), a component of green tea, inhibits human platelet aggregation and cytosolic [Ca2+]cincreases more strongly when these processes are induced by thrombin than by the non-proteolytic thrombin receptor activating peptide (TRAP), thromboxane mimetic U46619, or fluoroaluminate. In line with the previously demonstrated EGCG anti-proteolytic activity, a marked inhibition on aggregation is obtained by pre-incubation of thrombin with EGCG prior to addition to cellular suspension. The catechin also reduces cellular Ca2+ influx following thapsigargin-induced calcium emptying of endoplasmic reticulum, and the agonist-promoted cellular protein tyrosine phosphorylation. Both tyrosine kinases Syk and Lyn, immuno-precipitated from stimulated platelets, are greatly inhibited upon cellular pre-incubation with EGCG, which also inhibits the in vitro auto-phosphorylation and exogenous activity of these two enzymes purified from rat spleen. Both thrombin-induced aggregation and [Ca2+]c increase are reduced in platelets from rats that drank green tea solutions. It is concluded that EGCG inhibits platelet activation, by hindering the thrombin proteolytic activity, and by reducing the agonist-induced [Ca2+]cincrease through inhibition of Syk and Lyn activities.
Keywords: Epigallocatechin-3-gallate (EGCG); thrombin proteolytic activity; platelet cytosolic Ca2+; non-receptor tyrosine kinases